Research on Brand Internationalization Development Strategy of Multinational Enterprises under the Background of Digitalization (Journal of Interdisciplinary Insights, 2024)
Brand internationalization is the only way for enterprises to enter the international market and establish a global brand. In order to gain a competitive advantage in the international market, multinational enterprises need to pay attention to the importance of brand internationalization, especially in the digital age, by adopting effective marketing strategies in different cultures and countries to balance internationalization and localization has become an urgent matter. Therefore, by analyzing the impact of digital technology on brand internationalization, this paper aims to explore the brand positioning, promotion, management and localization strategies of multinational enterprises in the global market, and study the development strategies of brand internationalization of multinational enterprises in the digital era. Combined with typical case analysis, the application and effect of digital tools and platforms in the process of brand internationalization are revealed. The study found that digital technology not only changed the way brand communication and marketing, but also improved the efficiency and precision of brand management. Multinational companies need to find a balance between brand consistency and localization, and use digital technology to enhance the global competitiveness of their brands. This paper expands the research on the international development strategy of multinational brands and provides a reference for the formulation of multinational marketing strategies in the digital age.